The Sable for Evenk Reindeer Herders in Southeastern Siberia: Interplaying Drivers of Changes on Biodiversity and Ecosystem Services: Climate Change, Worldwide Market Econonomy and Extractive Industries - Lavrillier, Alexandra; Gabyshev, Semen; Rojo, Maxence (HAL CCSD, 2016)
International audience